The potential of ethanol extracts 96% mature Papaya fruit seeds (Carica papaya L) as anti-diarrhea medicine - Wilujeng Suciati; Sri Wahyu Basuki (Universitas Muhammadiyah Surabaya, 2022)
Mature papaya fruit seeds (Carica papaya L.) reduce diarrhea because of phytochemical compounds. This study aimed to determine the potential of 96% ethanol extract of mature papaya fruit seeds as antidiarrhea. This study used experimental laboratory research with pre and post-test with control group design. The research subjects were 25 mice divided into 5 groups, KI group (negative control), KII (positive control) loperamide, and KIII-KIV-KV given treatment with a dose (200 mg; 400 mg; 800 mg). A decrease in diarrhea is known by observing the consistency of feces, stool weight, and stool diameter. Data were analyzed by the Kruskal Wallis test and the Mann Whitney Post Hoc test. The results of the consistency of feces in group K(I) were compared with groups of K(II), K(III), K(IV), K(V) p=0.046, 0.083, 0.014, and 0.014. In stool weight K(I) compared to K(II), K(III), K(IV), K(V) with p=0.053, 0.102, 0.016, and 0.053. In the observation of absorption diameter K(-) compared to K(+), KI(200), KII(400), KIII(800) the p=0.121, 0.0197, 0.051 and 0.21. In conclusion, the mature extract papaya fruit seeds can reduce diarrhea seen from the stool consistency in the group extract 400 and 800 mg/Kilograms body weight and fecal weight in the 400mg/Kilograms body weight extract group.